(3ePcQGJ (B/s - (3NjQ GdOjf , eMeO s ((3GdLRGFQ (B;(3OjhGf GdeWHhYGJ (B:s (3GdeDSSIGdhWfjI ddcJGH ,s)
(3hdO GdTjN eMeO NjQ GdOjf aj TgQ OSeHQ SfI(B1902 (3aj HdOI aQaGQ hdGjI HScQI h ajgG GdbQBf GdcQje h HYV eHGOF GddZI h Gdabg bHd Cf jfJbd Gdi bSfWjfI djhGUd OQGSJg Ydi CSGJPI eYQhajf eKd GdeQMhe GdTjN YHO GdMejO Hf HGOjS h GdeQMhe GdWGgQ Hf RbhWI (B, (3h aj SfI (B1918(3SGaQ Gdi JhfS edJMbG HLGeY GdRjJhfI dJfejI eYdheGJg h GTHGY QZHGJg aj GdYdhe h GdeYGQa hHYO SHY SfhGJ Cj aj SfI (B1925(3JMUd Ydi TgGOI GdJWhjY h cGf JQJjHg GdKGfj ef NeSjf eQTMG (B.s
Keywords: (3ePcQGJ s